Use of incineration bottom ash in geotechnical applications - G. Hayshagen (Nanyang Technological University, 2022)
The primary aim of this project is to examine the feasibility of utilising incinerated bottom ash (IBA) as a partial replacement for Portland cement in deep cement mixing with marine clay (MC) by varying the proportion of IBA with cement in percentages of 20,40 and 60%. The outcome of this study indicates that IBA can be used as a partial replacement for Ordinary Portland Cement (OPC) but with an advised proportion of up to 20%. Unconfined Compression (UC) test was conducted to obtain the unconfined compression strength of IBA-OPC-MC matrix. Direct Shear Test was conducted to obtain the shear strength together with friction angle and cohesion. The compression strength of IBA-OPC-MC decreased as the percentage of IBA increased. Cohesion and friction angle generally decreases as the percentage of IBA increases. Hence, the IBA-OPC-MC matrix generally has lower compression strength than the OPC-MC matrix. Further studies can be done to determine the effect of cement content on the friction angle and cohesion of the IBA-OPC-MC matrix when IBA is increased.